Promosi Kesehatan oleh Kader dan Petugas Kesehatan tentang Pencegahan Penyakit Demam Berdarah Dengue di Kecamatan Umbulharjo, Kota Yogyakarta Health Promotion Model of Dengue Haemorrhagic Fever Prevention by Health Offic - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Discussion method of health promotion facilitated by health officer or cadre using folder is needed. The success of health promotion depends on the skill of the facilitator to modify the behavior of other individuals. The problem is whether or not a difference of the skill between health officer and cadre in increasing people's knowledge about DHF prevention. The research was aimed to find out the difference in people's knowledge of DHF prevention given by the officer and cadre. The research design was nonrandomized pretest-posttest control group. The subject of research were 30 mothers, given the promotion of DHF prevention by health officer and other 30 mothers were given by cadre. The technique of sampling was purposive sampling. The data were analysed using t-test. The results showed that both facilitators, health officer and cadre, increased the mothers' knowledge about DHF prevention. It was concluded that either health officer or cadre could increase mothers' knowledge about DHF prevention and there was no significant difference of promotion between health officer and cadre.